Islamic Education Learning Strategy in Mental Development of Mentally Disabled Children in Inclusive Schools of Medan City - Saiful Akhyar Lubis; Nurussakinah Daulay; Intan Kumalasari (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aimed to examine the Islamic Education Learning Strategy in the mental development of children with mental disabilities in inclusive schools in Medan City. In inclusive schools, Islamic education is distinct from other public schools. The Inclusive School of Medan City was the site of this investigation. The findings showed that planning, implementation, and evaluation all played significant roles in the Islamic Education learning method. Through the draft lesson plan, planning emphasizes the formation of religious characters (Ilahiyah) and moral development (Insaniyah). In order to improve the cognitive, affective, and psychomotor development of mentally challenged children, this program's implementation focuses on helping youngsters internalize Islamic teachings through stages such as habituation, example, and full mentoring. Teachers collaborate with parents by providing a format for the daily tasks of students with mental disabilities to help them learn the Koran, the practice of Shalat and prayer, morals (commendable deeds performed, fiqh), and other aspects of Islamic religious learning, such as the Koran, the practice of Shalat and prayer, and other aspects of Islamic religious learning (procedures for purification). Children with mental disabilities can develop a sound mind via the study of Islamic education.